Fresh air eases work—the effect of air quality on individual investor activity - Meyer, Steffen; Pagel, Michaela (Review of Finance, 2024)
Abstract This article shows that contemporaneous and lagged air pollution negatively affects the likelihood of German individual investors to log in and trade in their brokerage accounts, using intraday data and controlling for investor-, weather-, traffic-, and market-specific factors. A 1 SD increase in air pollution leads to a 1.3 percent reduction in the probability of logging in, which is larger than the response to a 1 SD increase in sunshine. We argue that changes in air pollution affect productivity in cognitively demanding tasks, such as trading. Our results are robust to macroeconomic productivity shocks, nonlinearities, or measurement error.